Evidence for rapid disc formation and reprocessing in the X-ray bright tidal disruption event candidate AT 2018fyk. Issue 4 (22nd July 2019) - Wevers, T; Pasham, D R; van Velzen, S; Leloudas, G; Schulze, S; Miller-Jones, J C A; Jonker, P G; Gromadzki, M; Kankare, E; Hodgkin, S T; Wyrzykowski, Ł; Kostrzewa-Rutkowska, Z; et al.
ABSTRACT: We present optical spectroscopic and Swift UVOT/XRT observations of the X-ray and UV/optical bright tidal disruption event (TDE) candidate AT 2018fyk/ASASSN–18ul discovered by ASAS–SN. The Swift light curve is atypical for a TDE, entering a plateau after ∼40 d of decline from peak. After 80 d the UV/optical light curve breaks again to decline further, while the X-ray emission becomes brighter and harder. In addition to broad H, He, and potentially O/Fe lines, narrow emission lines emerge in the optical spectra during the plateau phase. We identify both high-ionization (O iii ) and low-ionization (Fe ii ) lines, which are visible for ∼45 d. We similarly identify Fe ii lines in optical spectra of ASASSN–15oi 330 d after discovery, indicating that a class of Fe-rich TDEs exists. The spectral similarity between AT 2018fyk, narrow-line Seyfert 1 galaxies, and some extreme coronal line emitters suggests that TDEs are capable of creating similar physical conditions in the nuclei of galaxies. The Fe ii lines can be associated with the formation of a compact accretion disc, as the emergence of low-ionization emission lines requires optically thick, high-density gas. Taken together with the plateau in X-ray and UV/optical luminosity this indicates that emission from the central source is efficiently reprocessed into UV/optical wavelengths. Such a two-component light curve is very similar to that seen in the TDE candidate ASASSN–15lh, and is a natural consequence of a relativistic orbital pericentre.